Mathematical modeling in chemical engineering - Rasmuson, Anders 1951-; Andersson, Bengt 1947 June 15-; Olsson, Louise (Professor in chemical engineering); Andersson, Ronnie (Assistant professor in chemical engineering) (Cambridge University Press, 2014)
"The book is a solid introduction to mathematical modelling for a range of chemical engineering applications, covering model formulation, simplification and validation. It explains how to describe a physical/chemical reality in mathematical language and how to select the type and degree of sophistication for a model. Model reduction and approximate methods are presented, including dimensional analysis, time constant analysis and asymptotic methods. An overview of solution methods for typical classes of models is given. As final steps in model building, parameter estimation and model validation and assessment are discussed. The reader is given hands-on experience of formulating new models, reducing the models and validating the models. The authors assume the knowledge of basic chemical engineering, in particular transport phenomena, as well as basic mathematics, statistics and programming. The accompanying problems, tutorials, and projects include model formulation at different levels, analysis, parameter estimation and numerical solution"-- Provided by publisher.